Challenges and recent developments in solar tracking strategies for concentrated solar parabolic dish - Franch Maverick A. Lorilla; Renyl Barroca (Institute of Advanced Engineering and Science, 2022)
This contribution presents an overview of control strategies for parabolic dish concentrated solar power (PD-CSP) sun tracker technologies from the literature on different implementations. This paper also highlights the practical challenges in designing sun trackers for CSP applications. Solar radiation undergoes seasonal changes and transients from the cloud that is exceptionally challenging to manipulate. This paper may provide control engineers with technical information on high-precision solar dynamic tracking and optical accuracy by emphasizing the features, advantages, and limitations of different control techniques and algorithms. Implementation of efficient control strategies addresses concerns in amending dynamics and nonlinearities, thus improving the system responses and extending the operational timeline of CSP plants, which results in a reduced cost per kWh produced.